European public procurement law : the Public sector procurement directive 2014/24/EU explained through 30 years of case law by the Court of Justice of the European Union.: the Public sector procurement directive 2014/24/EU explained through 30 years of case law by the Court of Justice of the European Union. (2015) - Koninck, Constant de; Ronse, Thierry; Timmermans, William
No abstract available